Temperature-metabolism relations of two species of Sebastes from different thermal environments - Wilson, F.Ray; Somero, George; Prosser, C.L. (Comparative biochemistry and physiology. B, Comparative biochemistry, 1974)
1. 1. Oxidative and glycolytic enzymes were compared for Sebastes auriculatus, a shallow water species subject to the annual temperature cycle (22°C Summer, 12°C Winter), and S. miniatus, which occurs below the thermocline (10°C). 2. 2. Cytochrome oxidase activity of muscle from S. miniatus was 70% higher than from S. auriculatus at 10, 15 and 20°C. 3. 3. In cross temperature acclimation S. auriculatus showed a marked compensation in cold water, S. miniatus a small amount of acclimation in warm water. 4. 4. Lactate dehydrogenase and pyruvate kinase activities were similar in the two species both when taken from natural summer temperatures and after cross-acclimation.